2020
DOI: 10.1186/s13063-020-4226-2
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety assessment of different dosage of benznidazol for the treatment of Chagas disease in chronic phase in adults (MULTIBENZ study): study protocol for a multicenter randomized Phase II superiority clinical trial

Abstract: Background: Chagas disease (CD) continues to be a neglected infectious disease with one of the largest burdens globally. Despite the modest cure rates in adult chronic patients and its safety profile, benznidazole (BNZ) is still the drug of choice. Its current recommended dose is based on nonrandomized studies, and efficacy and safety of the optimal dose of BNZ have been scarcely analyzed in clinical trials.Methods/design: MULTIBENZ is a phase II, randomized, noninferiority, double-blind, multicenter internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 28 publications
1
38
0
5
Order By: Relevance
“…The BZN beneficial effect was not related to treatment period or daily dose, although this dosage is considered sub-dose by the current guidelines. Few studies addressed different BZN dose regimens, some with drugs association, but all of them used parasite load as a surrogate for efficacy and did not analyze patients’ clinical progression [ 25 , 28 , 29 , 33 ]. Also, changes in post-treatment serological curve occur only after a long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BZN beneficial effect was not related to treatment period or daily dose, although this dosage is considered sub-dose by the current guidelines. Few studies addressed different BZN dose regimens, some with drugs association, but all of them used parasite load as a surrogate for efficacy and did not analyze patients’ clinical progression [ 25 , 28 , 29 , 33 ]. Also, changes in post-treatment serological curve occur only after a long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in the 1990s and 2000s showed that trypanocidal treatment may promote some positive results on parasitemia, serology, and heart disease progression [ 23 , 24 ]. More recently, most clinical trials tested trypanocidal treatment efficacy by means of polymerase chain reaction (PCR) as the main parasitological outcome [25] , [26] , [27] , [28] , [29] . Similarly, observational studies followed the same outcome [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The BENEFIT study, the most extensive clinical trial with patients with CCC performed to date, showed that 192 (13.4%) of patients interrupted treatment during the study due to drug adverse events (AEs) ( Morillo et al., 2015 ). Thus, in recent years, new clinical studies are making efforts to find new strategies to decrease Bz dosage and even increase its efficacy ( Almeida et al., 2019 ; Molina-Morant et al., 2020a ; Torrico et al., 2021 ) to reduce the occurrence of adverse events, thus enhancing treatment compliance ( Ciapponi et al., 2020 ). On the other hand, efficacy of Bz treatment in progression of severity of CCC is still on debate ( Rassi et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Around 70% of patients still had positive lytic antibodies; some presented anti-T.cruzi IgG antibody titers and positive T. cruzi PCR findings (Alarcoń de Noya et al, 2011). Considering that Bnz is highly effective in the acute phase and during childhood in other endemic regions where other parasite DTUs prevail (Bianchi et al, 2015;Moscatelli et al, 2019), these data suggested therapeutic failure and consequently a second treatment was administered to people with persistence of lytic antibodies and/or positive PCR results, however without outcome improvement (Garcia-Bournissen, 2019;Molina-Morant et al, 2020).…”
Section: Introductionmentioning
confidence: 99%